A Silyliumylidene Cation Stabilized by an Amidinate Ligand and 4‐Dimethylaminopyridine. Issue 35 (12th July 2013) - Yeong, Hui‐Xian; Xi, Hong‐Wei; Li, Yongxin; Lim, Kok Hwa; So, Cheuk‐Wai
Abstract The synthesis and reactivity of a silyliumylidene cation stabilized by an amidinate ligand and 4‐dimethylaminopyridine (DMAP) are described. The reaction of the amidinate silicon(I) dimer [LSi:]2 (1; L=PhC(NtBu)2) with one equivalent of N‐trimethylsilyl‐4‐dimethylaminopyridinium triflate [4‐NMe2C5H4NSiMe3]OTf and two equivalents of DMAP in THF afforded [LSi(DMAP)]OTf (2). The ambiphilic character of 2 is demonstrated from its reactivity. Treatment of 2 with 1 in THF afforded the disilylenylsilylium triflate [L′2(L)Si]OTf (3; L′=LSi:) with the displacement of DMAP. The reaction of 2 with [KHB(iBu)3] and elemental sulfur in THF afforded the silylsilylene [LSiSi(H)(NtBu)2C(H)Ph] (4) and the base‐stabilized silanethionium triflate [LSi(S)DMAP]OTf (5), respectively. Compounds 2, 3, and 5 have been characterized by X‐ray crystallography.